Load–aware energy–efficient medium access control for Wireless Sensor Networks. (18th June 2012) - Chao, Chih–Min; Lee, Yi–Wei
In Wireless Sensor Networks (WSNs), sensors are usually battery–powered. Therefore, it is essential to reduce energy consumption to prolong network lifetime. In this paper, we propose a Load–aware Energy–efficient MAC protocol (LE–MAC) which utilises fuzzy control and the quorum concept. The LE–MAC protocol utilises fuzzy control to dynamically adjust the active/sleep ratio of each sensor node. The quorum concept is adopted to guarantee that two nodes with different active/sleep ratios can meet and communicate with each other. Simulation results verify that our LE–MAC can adapt to various network traffic loads. Furthermore, LE–MAC achieves significant performance improvements in energy consumption, transmission successful ratio, and transmission delay.